A novel LAMP2 initiation codon mutation causes Danon Disease: a case report - Li, Qingchuan; Sun, Zhihong; Qiu, Zeping; Chen, Yanjia; Jin, Wei (Frontiers in Cardiovascular Medicine, 2025)
Danon Disease (DD) is a rare X-linked inherited disorder caused by severe deficiency of lysosome-associated membrane protein-2 (LAMP-2), encoded by the LAMP2 gene. Characteristic clinical features include a triad of cardiomyopathy, skeletal myopathy and cognitive impairment in males. Females usually exhibit milder, cardiac-predominant manifestations later in life. In this case, we report a 30-year-old woman with a novel suspected pathogenic LAMP2 mutation (c.1A > T, initiation codon mutation). She developed Wolff-Parkinson-White (WPW) syndrome in her twenties, acute heart failure post cesarean section at age 29, and persistent left ventricular hypertrophy. Positive result of Technetium-99 m pyrophosphate (99mTc-PYP) scintigraphy strongly indicated transthyretin amyloid cardiomyopathy (ATTR-CM). However, whole-exome sequencing (WES) identified the novel A to T transition in initiation codon (c.1A > T) of LAMP2 gene, establishing the diagnosis of DD and revealing the false-positive result of PYP scintigraphy in DD.